Cellulose-stabilized oil-in-water emulsions: structural features, microrheology, and stability - Costa, Carolina (2021)
Cellulose-based oil-in-water (O/W) emulsions were studied by diffusing wave spectroscopy (DWS) regarding the effect of the cellulose concentration and mixing rate on the average droplet size, microrheological features and stability. Furthermore, the microstructure of these emulsions was imaged by cryo-scanning electron microscopy (cryo-SEM). The micrographs showed that cellulose was effectively adsorbed at the oil-water interface, resembling a film-like shell that protected the oil droplets from coalescing. The non-adsorbed cellulose that was observed in the continuous aqueous medium, contributed to the enhancement of the viscosity of the medium, leading to an improvement in the stability of the overall system. Generally, the higher the cellulose concentration and mixing rate, the smaller the emulsion droplets formed, and the higher was their stability. The combination of both techniques, DWS and cryo-SEM, revealed a very appealing and robust methodology for the characterization and design of novel emulsion-based formulations.